Musique quantique et temps ondulant. Pour une théorie ondulatoire de l’alouette - Lassus, Marie Pierre (BACHELARD STUDIES - ÉTUDES BACHELARDIENNES - STUDI BACHELARDIANI, 2024)
As an invisible art, music has a special relationship with time: ephemeral, it actualizes the present and stimulates life that soars, rises and falls like the bird whose songs manifests its “dazzling invisibility”. If it is true that time proceeds by leaps and bounds, leaping over useless durations as Bachelard thought when he placed music under the sign of the lark, it embodies a new reality in the twentieth century, plural and spatio-temporal, revealed by technical devices in this century, which saw the birth of electronic music. By proposing a wave theory of the lark that only the vibrating part of our being can understand, the philosopher suggests the idea of un music that would be both a quanta phenomenon and a special case of phenomenotechnics.